Evaluation of Acne Quality of Life and Clinical Severity in Acne Female Adults - Amal Kokandi (Dermatology Research and Practice)
Acne is a common disease especially among teenagers. It has a considerable psychological impact on affected individuals. The aim of this paper was to assess if the effect of acne on acne-related quality of life is correlated to acne clinical severity. 112 university female students attending the university medical clinics with acne complaints were examined. Cardiff Acne Disability Index (CADI) was used to assess acne-related quality of life, and global acne grading system (GAGS) was used to assess clinical severity of acne. There was no correlation between acne severity (GAGS scoring system) and quality of life impairment as assessed by CADI score (𝑟=0.145, 𝑃=.127). Additionally, CADI score did not correlate with disease duration or age of patients. We therefore conclude that acne clinical severity alone does not affect acne-related quality of life changes. Many other factors might play a role.